The role of climate change anxiety in shaping childrearing intentions among people living in British Columbia - Aran, Niloufar; Sharma, Aayush; Bratu, Andreea; Closson, Kalysha; Gislason, Maya K.; Kennedy, Angel; Logie, Carmen H.; Barkin, Jennifer L.; Hogg, Robert S.; Card, Kiffer G. (Frontiers in Public Health, 2025)
IntroductionClimate change concerns have emerged as a factor in shaping childrearing intentions. Given extreme weather events, climate change-related anxiety has increased drastically in the region of British Columbia (BC), Canada. This study explored how worry about an increasingly uncertain future may be associated with people’s childrearing intentions in BC.MethodsThis study used BC-CDMS (British Columbia Climate Distress Monitoring System) data from childless participants aged 16–44. We conducted multinomial logistic regression analyses (n = 441) to examine the association between climate change anxiety [measured using the Climate Change Anxiety Scale (CCAS)] and childrearing intentions. We controlled for covariates, including socio-demographic characteristics and generalized distress. A mediation analysis also tested whether political orientation mediates the primary relationship.ResultsParticipants who were undecided about having children (aOR = 1.58, 95% CI = 1.10–2.26) and those who planned not to have children (aOR = 1.64, 95% CI = 1.13–2.37) had higher CCAS scores compared to those who planned to have children. After controlling for covariates, climate change anxiety was still associated with childrearing intentions. Our mediation model indicated that political orientation scores partially mediate the relationship between climate anxiety and childrearing intentions.DiscussionDecision-makers should consider the impacts of climate anxiety and childrearing intentions on population and demographic shifts while supporting opportunities to reduce climate anxiety. Future research should consider the factors that influence and contribute to climate anxiety and climate-related distress, and their impact on childrearing intentions.